PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN KREATIVITAS TERHADAP MINAT BERWIRAUSAHA MELALUI EFIKASI DIRI SEBAGAI VARIABEL MEDIASI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NEGERI JAKARTA ANGKATAN 2022 - Frisca Regita Putri; Corry Yohana; Annisa Lutfia (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of entrepreneurship education and creativity on entrepreneurial interest through self-efficacy as a mediating variable in Students of the Faculty of Economics and Business, Jakarta State University, Class of 2022. The population in this study were students of the Faculty of Economics and Business, Jakarta State University, Class of 2022. The sampling technique used was non-probability sampling with a purposive sampling method, resulting in a sample size of 294 respondents. Data collection was carried out through a questionnaire using a Likert scale. This study used a Structural Equation Modeling (SEM) data analysis technique with a Partial Least Square (PLS) approach, which was analyzed using SmartPLS software version 4. The results of this study indicate that entrepreneurship education and creativity have a positive and significant influence on entrepreneurial interest. Furthermore, self-efficacy has been shown to mediate the influence of entrepreneurship education and creativity on entrepreneurial interest.